Impact of Business Development Services on Women Entrepreneur Performance with Managerial Support - Karmila, Yusri; Nuraini (Inovasi Analisis Data, 2025)
Purpose: Using data from a multi-stakeholder project in Cameroon, this paper investigates the direct and interactive effects of training and skills development, market access facilitation and business advisory services on the performance of women entrepreneur.Method: They employed a quantitative cross-sectional design and collected data via a structured questionnaire, adjusted from validated measures from earlier studies. Data were analysed using IBM SPSS 26 and analysed by multiple regression for direct effects and the PROCESS macro for moderation effects.Findings: Each of the three BDS components has significant positive impact-performance effects on entrepreneurs, with training and skills development rated as the most impactful of the three BDS components. Managerial support very significantly moderates all relationships suggesting that strong team leadership engagement enhances the value derived from BDS interventions.Novelty: Using the Resource-Based View and Capability Theory, this study provides unique empirical insight into the interplay of managerial support in maximizing the impact of BDS on women-led MSMEs. Answering a fundamental question that has been missing in previous studies, it examines the relationship between external service delivery and internal leadership capacity.Implications: Results highlight the need for combining leadership development with BDS in order to increase impacts. Fifth, policymakers and practitioners should focus on a multi-faceted approach to align incentives through external levers with capability-building efforts to promote sustainable growth in MSMEs.